UJI PERFORMANSI PEMANFAATAN PANAS KONDENSOR SISTEM KOMPRESI UAP 2 HP R-407c TERHADAP SISTEM ABSORPSI - Haryanto, Haryanto; Hidayati, Baiti (JURNAL TURBULEN, 2018)
The generating system of the Absorption Refrigeration Trainer with Solar Cell Panel Unit (RBA-ART-S) is one type of cooling systems. Working principle that exist in absorption system one of them using heater, while in vapor compression system, heat is discharged by condenser to environment. If the refrigerant in the absorption system gets additional heat from the condenser in the vapor compression system it will accelerate the heating of the refrigerant present in the absorption system. From the above statement, the authors do research on absorption machine with variation of heat source by using the heat from LPG gas and also with the addition of heat calorific source from the condenser of the vapor compression system, so that the heat from the condenser can be utilized. The parameters taken in this performance test are temperature. Based on the test results obtained niali COP in the absorption system by using LPG gas of 5.781 while the value of COP for the utilization of heat of condenser with LPG gas is 5.941. Thus the process of utilizing condenser heat and LPG gas (combinations) has a higher COP value, in other words there is an increase in performance with the utilization of exhaust heat from the condenser.Â Keywords: COP, Refrigeration, and Absorption